Metal-free hydroarylation of the side chain carbon–carbon double bond of 5-(2-arylethenyl)-3-aryl-1,2,4-oxadiazoles in triflic acid - Anna S. Zalivatskaya; Dmitry S. Ryabukhin; Marina V. Tarasenko; Alexander Yu. Ivanov; Irina A. Boyarskaya; Elena V. Grinenko; Ludmila V. Osetrova; Eugeniy R. Kofanov; Aleksander V. Vasilyev (Beilstein Journal of Organic Chemistry, 2017)
The metal-free reaction of 5-(2-arylethenyl)-3-aryl-1,2,4-oxadiazoles with arenes in neat triflic acid (TfOH, CF3SO3H), both under thermal and microwave conditions, leads to 5-(2,2-diarylethyl)-3-aryl-1,2,4-oxadiazoles. The products are formed through the regioselective hydroarylation of the side chain carbon–carbon double bond of the starting oxadiazoles in yields up to 97%. According to NMR data and DFT calculations, N4,C-diprotonated forms of oxadiazoles are the electrophilic intermediates in this reaction.